PENGEMBANGAN BAHAN AJAR ALAT INDERA MANUSIA BERBASIS MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMANDIRIAN BELAJAR MAHASISWA UNIVERSITAS ALMUSLIM BIREUEN - Novi Sari Liani; Erlia Hanum; Rahmawati; Cut Roswita (LPPM Universitas Cipta Mandiri, 2025)
This study aims to develop teaching materials for the human senses based on a problem-based learning model to enhance the learning independence of Umuslim Bireun students and to test their feasibility. This study employed a quantitative approach with Research and Development (R&D) methods. The ADDIE development model utilized analysis, design, development, implementation, and evaluation. The results of the media expert validation showed that the media aspects, technical quality, and media size achieved percentage values of 85.42%, 89.07%, and 93.92%, respectively, and were concluded as very good. The material expert analysis clearly demonstrated that the media coverage, accuracy, currency, and arousal of interest achieved percentage values of 88.96%, 84.87%, 90.13%, 83.84%, and 86.17%, respectively, and were concluded as very good. The results of the linguist analysis clearly show that in terms of clarity, suitability to student development and suitability to language rules with a percentage value of 84.46%, 86.75%, 95.32%. The results of the overall feasibility test for individual, group and field validation with a percentage of 90%, 89% and 95% qualifications are very adequate. The results of the gain normality test analysis obtained a result of 0.87 so it can be concluded that there is an increase in learning independence of Umuslim students with human sensory learning materials based on the problem-based learning model.